Migrant child phenomenon in China: Subjective happiness factors for assessing service needs. (July 2018) - Xu, Limin; Cheung, Monit; Leung, Patrick; Xu, Yongxiang
Abstract: In Tianjin, China, 476 migrant children responded to a survey on educational processes and family influences. These children reported a fair-to-good subjective happiness level. A sequential regression model shows that their subjective happiness will rise alongside nine improvements: (1) public school enrollment, (2) nondiscriminatory admission to education, (3) targeted assistance for higher grade students, (4) integrated local-migrant classes, (5) teacher-student interactions, (6) extracurricular activities, (7) academic performance, (8) parent-child communication, and (9) friends in the city. A comprehensive assessment index can be developed to incorporate school-home factors with a dual focus : migrant worker welfare and migrant child development. Highlights: The migrant child phenomenon in China is connected to the country's effort to encourage economy recovery. Migrant children's subjective well-being is related to their adjustment to a new school-home environment. Nine school-home connection factors can help design integrative services for migrant families.